A framework for capturing heterogeneity, heteroskedasticity, non-linearity, reference dependence and design artefacts in value of time research. (February 2017) - Hess, Stephane; Daly, Andrew; Dekker, Thijs; Cabral, Manuel Ojeda; Batley, Richard
Highlights: Reports methodological innovations and results for 2014/2015 GB national VTT study. First GB study of its kind in 20 years. Important new modelling developments and improvements to practice. Abstract: In early 2014, the UK Department for Transport (DfT) commissioned the first national value of travel time (VTT) study since the mid-1990s. This paper presents the methodological work undertaken for this study, with important innovations along a number of dimensions, both in terms of survey design and modelling methodology. Our findings show a rich pattern of heterogeneity across the travelling public, in terms of an impact on the VTT by both person and trip characteristics, as well as a major role for a number of characteristics that relate to the specific choices faced in a hypothetical stated choice setting, including reference dependence and non-linearities in sensitivities. We also discuss how these behavioural values were translated into values for use in appraisal, and the challenges faced when doing this on the basis of results obtained with advanced models.